Heavy Metals (Cd, Cu and As) Accumulation by Aquatic Plant along with Gomti River, Lucknow (U. P.) - Anurag Kumar Singh; N. K. S. More; Pashupati Nath (G-Journal of Environmental Science and Technology, 2014)
The aquatic plants have a great importance to the removal of heavy metals from the contaminated river water. In this study the heavy metals (Cd, Cu and As) were evaluated in aquatic plants like Ranunculus sceleratus, Hydrilla virticillata, Botumusumbelatus and Sagittaria japonica collected from the 15 sites along with Gomti river, Lucknow (U. P.), Heavy metals enters into the river through the discharge of domestic sewage, industrial effluents, municipal waste water etc., The concentration of Cu was found maximum followed by Cd and least was As for all selected plants at all sites. The highest accumulation of Arsenic, Cadmium and Copper was found in Hydrilla virticillata (0.172±0.005 μg g−1 DW), Sagittaria japonica(1.62±0.02 μg g−1 DW) and Botumus umbelatus (2.08±0.07 μg g−1 DW) respectively. However, the lowest concentration of all these heavy metals was observed in Ranunculus scleratus sp. The results of this study to give the information in relation to aquatic plants growing in polluted water, which accumulates heavy metals. These findings provide are an opportunity for the removal of toxic heavy metals from the use of aquatic plants in phytoremediation and treating water bodies.